SOME FACTORS INFLUENCING THE EMPLOYERS’ PERFORMANCE AT THE ADMINISTRATION OF POLITEKNIK NEGERI SRIWIJAYA THROUGH USER EVALUATION - Irma Salamah (Journal of Economics, Business, and Accountancy Ventura, 2013)
The user evaluation is a wide construct where the evaluation is on an evaluation or measurementof individual attitudes and beliefs towards both goods and services. Evaluation of the users’technology-task fit is an important thing related to the achievement of individual performance. Asproposed the construct of technology-task fit to serve as a benchmark for measuring the userevaluations of information systems. This research refers to studies that have been conducted bythe previous researchers on individual performance to be verified by the expectation if the tasktechnologyfit can give a positive value for the user evaluation. As assumed, there is a positiverelationship when increasing individual performance, in which this study is focused on employeeperformance at Polsri administration. The sample consists of 64 employees at Polsri administration.The results show the characteristics of technology, individual, and technology-individualinteractions having positive and significant impact on user evaluation. The characteristics of thetask and the task-technology interaction have no significant effect negatively on user evaluation.However, the user evaluation has positive effect significantly on performance.